2020
DOI: 10.3390/su12041581
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Masonry Made from Recycled Aggregates: LCA Case Study

Abstract: For a sustainable building industry, reusable construction with a low demand for primary resources is needed. Moreover, if we want to reduce the amount of construction and demolition waste, construction with recycled aggregate should be considered. To investigate the environmental impacts of such concrete construction, life cycle assessment (LCA) was used to compare the following types of concrete construction: Reusable blocks with recycled brick aggregate, reusable blocks with recycled concrete, reusable bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The cost of shipping would easily make Italian crushed bricks more costly than local alternatives, and the environmental impacts for delivering such bulky and heavy material would quickly exceed local options (Estanqueiro et al., 2018). It is thus important for material scientists and engineers to research a more sustainable alternative approach that will enhance closed‐loop recycling and allow the reuse of bricks as structural elements within the country of origin (Lederer, Gassner, Kleemann, et al., 2020; Pešta et al., 2020).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The cost of shipping would easily make Italian crushed bricks more costly than local alternatives, and the environmental impacts for delivering such bulky and heavy material would quickly exceed local options (Estanqueiro et al., 2018). It is thus important for material scientists and engineers to research a more sustainable alternative approach that will enhance closed‐loop recycling and allow the reuse of bricks as structural elements within the country of origin (Lederer, Gassner, Kleemann, et al., 2020; Pešta et al., 2020).…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The most assessed CE definition, using the R-imperatives as measure, was recycling (n = 36), followed by reuse (n = 32), with the least being not represented at all (refuse, rethink, repair, reduce, remanufacture, and along with 'downcycling) (n = 0) (see Figure 8b). A number (n = 12) of studies assessed several imperatives, e.g., [32], who assesses case studies applying upcycling and Design for Disassembly (DfD) respectively; [36], whose circular design case applies DfD principles with the options of reuse, recycling, and recovery; [37], who assesses reusable masonry blocks produced from recycled CDW; and [38], whose guidelines are derived from case studies on 'the circular kitchen', assessing various circular value retention processes (VRPs), e.g., a variant designed with recycled contents and one enabling reuse of the single components. Diving into the content of the papers, Figure 8a, it was found that the scales most predominantly assessed in the case studies were materials (n = 28), followed by components (n = 18), with the least being neighbourhood and/or city, both with (n = 1).…”
Section: Synthesis Of Included Studiesmentioning
confidence: 99%
“…Studies indicate that sustainable natural building materials reduce the consumption of natural materials and the environmental impact caused by the extraction, transportation, and processing of materials. Some studies have indicated that the use of natural materials reduces the greenhouse gases emitted from buildings by 56.6% during the life of the building [11].experimental studies investigated the use of natural and waste materials in building construction such as agricultural waste [12,13,14,15,16], construction waste [17,18,19] Studies have proven that the heat gain by 21% and reduce indoor temperatures of residential spaces by 25% [11] which leads to improved thermal conditions, and thus these materials reduce energy consumption. Also, Studies have indicated that the building envelope is the largest contributing factor to thermal comfort within residential spaces; as such, many different types of bricks in the external walls cement bricks could lead to lower electricity consumption by 12.8% [20], gypsum-covered clay panels have been found to reduce temperatures 2.5 K compared traditional brick walls [21].…”
Section: Introductionmentioning
confidence: 99%